Asuhan Keperawatan Kritis Pada Pasien Chronic Kidney Disease CKD Dengan Intervensi Inovasi Memberikan Nutrisi Enteral Menggunakan Metode Intermiten Feeding Untuk Mengurangi Produksi Residu Lambung di Ruang ICU RSU Kabupaten Tengerang - Aef Eka Saputra; Zahrah Mauilidia Septimar; Andi Setiyawan (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
Background: Critical care developed starting from a need for patients experiencing life-threatening illnesses that could be better met if the patient was cared for in a different room. Chronic Kidney Disease (CKD) is defined as a decrease in kidney function characterized by a glomerular filtration rate (GFR) < 60 ml/min/1.73 m2 that occurs for more than 3 months (Mahesvara, 2020). Nutrition is an important part of the management of critical patients such as those suffering from advanced Chronic Kidney Disease (CKD). Providing nutrition to critical patients is to encourage the healing process. Inaccuracy in administering enteral nutrition can cause complications such as high gastric residual volume, gastric retention, diarrhea, nausea and vomiting. High gastric residues during enteral nutrition increase the risk of pulmonary aspiration which is the most severe complication of enteral nutrition. Intermittent feeding is one method of providing enteral nutrition to prevent these complications. The aim of this research is to provide comprehensive nursing care for patients with Chronic Kidney Disease (CKD). This writing method uses patient intervention and observation carried out for three days, to determine the patient's condition and provide appropriate nursing care which is then documented. Results: Based on the results of the intervention and monitoring carried out, it can be concluded that there are differences in the conditions of gastric residue production before and after the enteral feeding intervention using the intermittent feeding method. With the result criteria of maintaining nutritious food intake increases. Conclusion: In critical patients there is a slowdown in gastric emptying and intestinal motility so that if enteral nutrition is given quickly into the stomach there will be an increase in gastric residue. Nursing action as an evidence base that can be given is in the form of providing enteral nutrition using the intermittent feeding method so that the stomach can be better prepared to receive nutrition because it is given gradually, a stomach that is not completely filled will be able to digest food better and the stomach will empty more quickly, thereby reducing the risk of aspiration.